Impact of silinity levels, gibberellin and prolin on some vegetative characteristics and qualities on chard plant (Beta vulgaris sub sp. cicla) - Mahdi I. H.; Madhoor H. A. A. (Al-Qadisiyah Journal of Pure Science, 2018)
An experiment was conducted in the winter season of the year (2012 - 2013) in a private Al-Hur district in Karbala governorate, to study the effect of irrigation with salt water and sprayingwith gibberellic and proline acids and their interaction on some vegetative and quality characteristics of chard plant (Beta vulgaris sub sp. cicla) grown in saline soil. The design of the experiment was randomized complete blocks (RCBD) in a factorial arrangement with three replications. The first factor was three levels of saline water (2, 4 and 6) ds. L-1 in addition to the river water as a control. The second factor was three concentration of each of GA3 and proline (50, 100 and 150) mg. L-1 in addition to the river water as a control. Means were compared by using averages revised least significant difference (RLSD) at 0.05 probability level when the treatments referred to significant effect. Results showed:1- Negative effect of salinity levels on the qualities of the vegetative plant chard.2- Increas of N% by impact of salinity level 2 ds. L-1 and K% increased with silinity level of salinity 2 ds. L-1, as well as the potassium% content of the leaves with a salinity 4ds. L-1.3 - Gibberellic acid was dominant on proline acid in terms of chard plant by 150 mg.L-1 concentration while proline acid was dominant on gibberellic acid with 100 mg. L-1 concentration.4- The interaction between the salinity levels and acids concentrations add showed a significant difference in most of the traits of the plant, especially in combinations consisting of level 2 ds. L-1 or comparison of saline with gibberellic acid by 150 mg. L-1 before flowering and 50 or 100 mg. L-1 after flowering while gave a combination of salinity level 4 ds. L-1 with concentration of proline acid 100 mg.L-1 higher content of potassium% leaves.